Integrated Primary Health Care Systems: A Potential Strategy for Enhancing Non-Communicable Disease Service Provision in Sumbawa District, West Nusa Tenggara - Listyati Budi Utami (BKM Public Health and Community Medicine, 2024)
Purpose: This study aims to identify barriers and explore effective strategies for increasing screening coverage for non-communicable diseases (NCDs), particularly cardiovascular disease, among the elderly at Posbindu PTM in Sumbawa District through innovative integration of primary healthcare services. Content: Cardiovascular disease represents a significant global and national health threat, causing over 17.8 million deaths annually. In Indonesia, the prevalence of cardiovascular disease is 1.5% and rising, making it the leading cause of death, particularly among men over 45 and women over 50, with an annual mortality rate of 650,000. In NTB, 30% of the population is at risk. The low coverage of Posbindu PTM services presents a substantial challenge to preventing and managing NCDs. Barriers include community reluctance to regularly visit Posbindu, a lack of awareness and understanding of NCDs, and limited human and health facility resources. The innovative integration of cardiovascular disease screening services into community health centers through the Posyandu Prima (Integrated Primary Services) concept addresses these barriers by increasing coverage and simplifying access to comprehensive health services for the elderly. This integration enhances elderly participation in cardiovascular disease screening and facilitates early detection of risk factors such as hypertension and high cholesterol, enabling more efficient and effective intervention. Collaboration between health workers at Posbindu and community health centers further enhances service efficiency and effectiveness. However, challenges persist, including operational adaptations and changes in the habits of elderly individuals who are unaccustomed to integrated services. Success hinges on government policies, specialized training for health workers, and effective educational campaigns targeting the elderly. While the integration of Posbindu PTM with community health centers offers a promising solution, achieving optimal results requires a multifaceted approach. This includes an integrated health service strategy, heightened public awareness through education, and the enhanced capacity of health workers to overcome barriers and achieve broader, more effective service coverage.